Perlawanan WALHI terhadap Rencana Pembangunan PLTN di Bangka Tengah: Strategi Politik Ekstra-Parlementer dalam Advokasi Lingkungan - Hijriyanto; Revana; Elza Putri; Marta Arya (STAI DDI Kota Makassar, 2026)
This study examines the resistance of the Indonesian Forum for the Environment (WALHI) against the planned construction of a Nuclear Power Plant (PLTN) in Central Bangka through an extra-parliamentary political perspective. The background of this study is the emergence of public resistance to development projects that are considered to have the potential to cause ecological, social, and economic risks, as well as minimal public participation in the policy-making process. This study aims to analyze the forms of WALHI's resistance and the extra-parliamentary political strategies constructed and practiced in environmental advocacy. The method used is a qualitative approach with a case study type, through data collection techniques such as interviews, observation, and documentation. The results show that WALHI's resistance is carried out through policy advocacy, public campaigns, community mobilization, and the use of mass media and social media in building public opinion. In addition, the extra-parliamentary political strategies implemented include framing environmental issues, producing counter-knowledge (counter-expertise), strengthening grassroots movements, and political pressure on the government and corporations. These findings indicate that WALHI plays a role as a political actor outside parliament that is able to influence public policy and fight for environmental justice. Thus, extra-parliamentary movements have become an important instrument in strengthening civil society participation in democracy and oversight of development policies.